2006
DOI: 10.1111/j.1526-4610.2006.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin in Trigeminal Ganglia of Female Rodents: Relevance to Menstrual Migraine

Abstract: Objectives.-We examined changes in the serotonin system across the estrous cycle in trigeminal ganglia of female rodents to determine which components are present and which are regulated by the variations in levels of ovarian steroids that occur during the estrous cycle.Background.-Migraine is 2-3 times more prevalent in women than in men and attacks are often timed with the menstrual cycle, suggesting a mechanistic link with ovarian steroids. Serotonin has been implicated in the pathogenesis of migraine, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 86 publications
2
28
0
Order By: Relevance
“…40,41 Serotonin vasoconstricts the nerve endings and blood vessels and in this way affects nociceptive pain. 42 Comings 43 postulated that low serotonin levels dilate blood vessels and initiate migraine.…”
Section: Serotonergic Neurotransmitter Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 Serotonin vasoconstricts the nerve endings and blood vessels and in this way affects nociceptive pain. 42 Comings 43 postulated that low serotonin levels dilate blood vessels and initiate migraine.…”
Section: Serotonergic Neurotransmitter Systemmentioning
confidence: 99%
“…It has been found that most of the neurons present in the dorsal raphe (site of emergence of trigeminal nerve) and trigeminal ganglia are serotonergic. 10,40,44 Serotonin (5-hydroxytryptamine, 5-HT) synthesis involves the rate limiting enzyme, tryptophan hydroxylase (TPH) 45 and is mainly degraded by the action of monoamine oxidases. 46 Tryptophan hydroxylase activity in rat brain base arteries has been suggested to be a marker of serotonergic innervations.…”
Section: Serotonergic Neurotransmitter Systemmentioning
confidence: 99%
“…Limited data imply that this may have a genetic basis. 58 It has been suggested that when estrogen levels peak, increased neuronal excitability is balanced by homeostatic gene regulation in the brain cortex and nociceptive systems. As levels fall around menstruation, a mismatch in homeostatic gene regulation by estrogen unmasks non-nuclear mitogenactivated hyperexcitability of cell membranes, sensitising neurons to triggers that activate migraine attacks.…”
Section: Studymentioning
confidence: 99%
“…Furthermore, the administration of estrogen upregulates 5-HT synthesizing enzyme, i.e. tryptophan hydroxylase [55,56], downregulates SERT upon shortterm treatment [57], whereas upregulates SERT following long-term treatment [58], decreases the expressions of 5-HT metabolizing enzyme, i.e., monoamine oxidase [59], and reduces the expression of 5-HT 1A receptor in the various regions of brain [60,61]. Therefore, estrogen modulates both the density of 5-HT receptors and 5-HT turnover [62,63].…”
Section: Discussionmentioning
confidence: 99%